2020
DOI: 10.3390/cancers12020472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diphtheria Toxin-Based Gene Therapy for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a major global malignancy, responsible for >90% of primary liver cancers. Currently available therapeutic options have poor performances due to the highly heterogeneous nature of the tumor cells; recurrence is highly probable, and some patients develop resistances to the therapies. Accordingly, the development of a novel therapy is essential. We assessed gene therapy for HCC using a diphtheria toxin fragment A (DTA) gene-expressing plasmid, utilizing a non-viral hydrodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…In a study conducted by Kamimura and his colleagues, a diphtheria toxin fragment A (DTA) gene-expressing plasmid was transferred using the hydrodynamics-based procedure. The results demonstrated a substantial inhibition of hepatocellular carcinoma occurrence in mice treated with hydrodynamic-based gene therapy 0 and 2 months after gene delivery [128]. Since ultrasound microbubble sonoporation have shown great potential for gene delivery, a ternary nanodroplet composed of perfluoropentane/C9F17-PAsp(DET)/miR-122/PGA-g-mPEG (PFP-7TNDs/miR-122) was prepared and evaluated for the transferring of microRNA-122 (miR-122) for hepatocellular carcinoma treatment.…”
Section: Liver Cancer Therapymentioning
confidence: 88%
“…In a study conducted by Kamimura and his colleagues, a diphtheria toxin fragment A (DTA) gene-expressing plasmid was transferred using the hydrodynamics-based procedure. The results demonstrated a substantial inhibition of hepatocellular carcinoma occurrence in mice treated with hydrodynamic-based gene therapy 0 and 2 months after gene delivery [128]. Since ultrasound microbubble sonoporation have shown great potential for gene delivery, a ternary nanodroplet composed of perfluoropentane/C9F17-PAsp(DET)/miR-122/PGA-g-mPEG (PFP-7TNDs/miR-122) was prepared and evaluated for the transferring of microRNA-122 (miR-122) for hepatocellular carcinoma treatment.…”
Section: Liver Cancer Therapymentioning
confidence: 88%
“…With this aim, we applied the hydrodynamic gene delivery (HGD) method, which has been used successfully to develop mice liver cancer in vivo by delivering oncogenes, including Yap , Ras , and Myc, to the liver 11 , 12 , 13 . To utilize this method, we established pancreas-targeted HGD to wild-type rats.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have shown that YAP overexpressed liver in wild-type mice showed the development of huge HCC in the short term and the tumors were heterogeneous, histologically [ 18 ]. Interestingly, HBx transgenic mice increase YAP protein expression postnatally in the hepatocytes, and YAP accumulation in the nucleus resulted in the hepatocytes’ carcinogenesis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HBx transgenic mice increase YAP protein expression postnatally in the hepatocytes, and YAP accumulation in the nucleus resulted in the hepatocytes’ carcinogenesis [ 12 ]. Therefore, it is reasonable to hypothesize that the HBx-YAP axis is involved in the HBV-related HCC occurrence and development of huge tumors and poor prognosis in HBV-related HCC [ 18 ]. Since there are no reports assessing the HBx and YAP expression patterns in HCC tumor and peritumor tissue with clinical information, we have assessed the HBx and YAP expression in human HBV-related HCC samples and their association with tumor size, histological findings, serum tumor markers, and prognosis, comparing them with HCC related to other etiologies.…”
Section: Introductionmentioning
confidence: 99%